DEVELOPMENT OF LOW-COST OPTICAL SENSOR-BASED DEVICE FOR REAL-TIME MICROALGAE CONCENTRATION MEASUREMENT - Syafutra, Heriyanto; Rustami, Erus; Claudia, Stephanie; Hardiningtyas, Safrina Dyah; Supriyanto, Supriyanto; Zuhri, Mahfuddin (Universitas Mataram, 2025)
Conventional methods for measuring microalgae concentration in water require several steps and must be carried out in the laboratory. These measurements are usually performed by counting microalgae filaments under an optical microscope using the Sedgewick Rafter Counting (SRC) method or by spectroscopy, utilizing light absorption by microalgae's chlorophyll. In this study, we propose an innovative and portable spectroscopic device for real-time measurement of microalgae concentration by integrating a light-dependent resistor (LDR) sensor and a microcontroller-based processing unit. The microalgae used in this study were Spirulina, a filamentous microalga from the class Cyanophyceae. The SRC method was used as a reference for measuring Spirulina concentration. UV-Vis spectroscopy data showed that the absorption of chlorophyll a and b was in the range of 400 - 450 nm. The absorption coefficients obtained from the UV-Vis absorbance vs. concentration relationship were in good agreement with those obtained from the logarithmic light intensity vs. concentration relationship across all tested predictive models. We confirmed that the emission spectrum of the LED used was aligned with the dominant absorption of Spirulina chlorophyll, ensuring accurate optical detection of microalgae concentration. The developed device demonstrated rapid estimation of microalgae concentration, with an average accuracy of more than 75%. This study showed that a portable and low-cost microalgae concentration measurement system can be developed using optical sensors and microcontrollers as an alternative to laboratory-based measurements. In addition, the designed device can be integrated with Internet of Things (IoT) platforms, enabling real-time monitoring of environmental conditions for applications such as water quality assessment, aquaculture, and biofuel production.